Exposure to family planning messages and teenage pregnancy: results from the 2017 Philippine National Demographic and Health Survey - Veincent Christian F. Pepito; Arianna Maever L. Amit; Clinton S. Tang; Luis Miguel B. Co; Neil Andrew K. Aliazas; Sarah J. De Los Reyes; Raymundo S. Baquiran; Lourdes Bernadette S. Tanchanco (BMC, 2022)
Plain language summary Adolescent pregnancy is associated with adverse health, psychosocial, and economic outcomes. As of 2017, the proportion of women aged 15-19 who have begun childbearing in the Philippines is 9%. To counter this, the Philippine government and its partners in the private sector disseminate family planning and contraception information to the general population. Thus, we studied the effect of being exposed to these family planning and contraception information in different forms of media and their effect of teenage pregnancy. We analysed the 2017 Philippine National Demographic and Health Survey. After controlling for the effect of other variables, we found that these family planning and contraception information had little effect on teenage pregnancy in the country. These findings highlight the need to improve the content and key messages of contraceptive and family planning messages, and improve their coverage in the general population.